Spatial-temporal analysis of carbon benefit and land use for low-carbon development strategies in Shandong Province, China - Hui Wen; Ziyu Zhong; Xujie Kong; Jichun Wang; Renqiang Li; Zhaosheng Wang; Shulin Yu; Zhen Xu; Hexin Chen; Qi Zhu; Pan Wang; Jiaquan Duan; et al. (Environmental Research Communications)
Assessing the carbon sequestration capacity of regional ecosystems is essential for achieving carbon neutrality goals. However, existing research often fails to comprehensively evaluate the spatial-temporal dynamic changes of ecosystem carbon emission and absorption. This study introduces a Carbon Benefit Index (CBI) to assess carbon neutrality potential and classifies Shandong’s 16 cities into four regions based on their carbon storage and emission profiles. We conducted an in-depth analysis of ecosystem carbon benefit in Shandong Province from 2000 to 2020 using the multimodel random forest ensemble method, which enhances the accuracy of carbon sink simulations across terrestrial ecosystems. Our results showed that from 2000 to 2020, Shandong’s carbon emission increased by 1.45 × 10 ^8 tons (a 203.8% rise), while carbon storage decreased by 3.40 × 10 ^7 tons (a 2.05% decline). Compared to previous studies, our findings underscore the significance of both above-ground and below-ground carbon storage. Grey correlation analysis of land use, anthropogenic CO _2 emission, and ecosystem carbon storage revealed that cultivated and forest lands were most significantly correlated with carbon storage, whereas built-up areas were most closely linked to carbon emission. The CBI analysis and classification of the 16 cities into four categories highlights the spatial-temporal heterogeneous of the carbon efficiency, and diverse roles cities play in the province’s overall carbon balance, informing city-specific, targeted carbon reduction strategies. The study emphasizes the need for spatially differentiated, comprehensive carbon accounting to improve carbon efficiency. Based on these findings, we propose tailored low-carbon improvement strategies for different regions. This research not only contributes to existing literature by incorporating below-ground carbon storage but also provides valuable insights for policy and land management, with practical implications for promoting sustainable development and advancing efforts toward carbon neutrality.